The Aggression Questionnaire: A validation study in student samples. - Pérez, Nieves; Ramos, Manuel M.; Reyes, A.; Robles, Humbelina; García-león, Ana; Vila, Jaime (The Spanish Journal of Psychology, 2002)
Sin resumen